Do People Know What They're Like in the Moment?. (March 2019) - Sun, Jessie; Vazire, Simine
Knowing yourself requires knowing not only what you are like in general (trait self-knowledge) but also how your personality fluctuates from moment to moment (state self-knowledge). We examined this latter form of self-knowledge. Participants (248 people; 2, 938 observations) wore the Electronically Activated Recorder (EAR), an unobtrusive audio recorder, and completed experience-sampling self-reports of their personality states four times each day for 1 week. We estimated state self-knowledge by comparing self-reported personality states with consensual observer ratings of personality states coded from the EAR files, which formed the criterion for what participants were "actually" like in the moment. People had self-insight into their momentary extraversion, conscientiousness, and likely neuroticism, suggesting that people can accurately detect fluctuations in some aspects of their personality. However, the evidence for self-insight was weaker for agreeableness. This apparent self-ignorance may be partly responsible for interpersonal problems and for blind spots in trait self-knowledge.